An Ontology Based Natural Language Processing Pipeline for Brazilian COVID-19 EMR - Gritz, Raquel A. J.; Pereira, Rafael S.; Silva, Henrique Matheus F. da; Zatti, Henrique G.; Viana, Laura E. A.; Navarro, Karol C. S. F.; Dias, Thalita R.; Oliveira, Viviane S. B.; Souza, Ricardo A.; Oliveira, Vinícius A.; Barral Netto, Manoel; Porto, Fabio (Anais do Brazilian e-Science Workshop (BreSci), 2021)
COVID-19 became a pandemic infecting more than 100 million people across the world and has been going on for over a year. A huge amount of data has been produced as electronic medical records in the form of textual data because of patient visits. Extracting this information may be very useful in better understanding the COVID-19 disease. However, challenges exist in interpreting the medical records typed as free text as doctors may use different terms to type in their observations. In order to deal with the latter, we created an ontology in Portuguese to describe the terms used in COVID-19 medical records in Brazil. In this paper, we present a brief overview of the ontology and how we are using it as the first step of a more complex NLP task.